KEPERCAYAAN DAN KEPUASAN KONSUMEN SEBAGAI JEMBATAN MEMPERKUAT LOYALITAS ATAS LAYANAN JNE EXPRESS - Oky Azka Meirina; Dwi Suryanto Hidayat (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this research is to determine the effect of service quality on loyalty through trust and customer satisfaction. The data used in this study is primary data based on 100 samples taken by accidental sampling method. The data is processed using Partial Least Square (PLS) software on the SmartPLS 3.2.9 data processing application. The results of the study prove that service quality has a positive and significant influence on consumer trust and satisfaction and consumer loyalty. The study also found that trust and satisfaction partially mediate the effect of service quality on consumer loyalty. This shows that the quality of service provided so far has been appropriate and able to foster trust and satisfaction in consumers and make consumers want to continue to use the services offered by JNE Express.